IMPLIKASI PELATIHAN MITIGASI BENCANA TERHADAP KESIAPSIAGAAN MASYARAKAT MENGHADAPI BENCANA GEMPA DI LEMBANG - Mulyono, Dinno; Elshap, Dewi Safitri; Kartika, Prita (IKIP Siliwangi Bandung, 2020)
This study aims to describe the impact of disaster mitigation training on community attitudes in dealing with disasters in the Lembang Region, West Java. The theoretical basis used in this research is the theory of community empowerment, community education and disaster mitigation. While the research method used is descriptive qualitative research with a sample of 30 people, the instruments used are surveys, interviews, observation and documentation study. The results of the study indicate that there are changes that are quite good, so that disaster mitigation training is good to be implemented. With the conclusion, that disaster mitigation training is important to develop public awareness and preparedness in dealing with disasters.